Characterization of a Cryopreserved Split-Thickness Human Skin Allograft–TheraSkin. (September 2016) - Landsman, Adam; Rosines, Eran; Houck, Amanda; Murchison, Angela; Jones, Alyce; Qin, Xiaofei; Chen, Silvia; Landsman, Arnold R.
ABSTRACT: OBJECTIVE: The purpose of this study was to examine the characteristics of a cryopreserved split-thickness skin allograft produced from donated human skin and compare it with fresh, unprocessed human split-thickness skin. BACKGROUND: Cutaneous wound healing is a complex and organized process, where the body re-establishes the integrity of the injured tissue. However, chronic wounds, such as diabetic or venous stasis ulcers, are difficult to manage and often require advanced biologics to facilitate healing. An ideal wound care product is able to directly influence wound healing by introducing biocompatible extracellular matrices, growth factors, and viable cells to the wound bed. MATERIALS AND METHODS: TheraSkin (processed by LifeNet Health, Virginia Beach, Virginia, and distributed by Soluble Systems, Newport News, Virginia) is a minimally manipulated, cryopreserved split-thickness human skin allograft, which contains natural extracellular matrices, native growth factors, and viable cells. The authors characterized TheraSkin in terms of the collagen and growth factor composition using ELISA, percentage of apoptotic cells using TUNEL analysis, and cellular viability using alamarBlue assay (Thermo Fisher Scientific, Waltham, Massachusetts), and compared these characteristics with fresh, unprocessed human split-thickness skin. RESULTS: It was found that the amount of the type I and type III collagen, as well as the ratio of type I to type III collagen in TheraSkin, is equivalent to fresh unprocessed human split-thickness skin. Similar quantities of vascular endothelial growth factor, insulinlike growth factor 1, fibroblast growth factor 2, and transforming growth factor β1 were detected in TheraSkin and fresh human skin. The average percent of apoptotic cells was 34.3% and 3.1% for TheraSkin and fresh skin, respectively. CONCLUSIONS: Cellular viability was demonstrated in both TheraSkin and fresh skin.